Strategi Sinergi Pendanaan Penanggulangan Kemiskinan dan Pengangguran di Kota Cilegon - Ali Irfan, Muhammad (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
Zakat, Infak, and Sedekah (ZIS) have the potential to be an extensive resource that has not been fully utilized. Government support is vital because it is in line with the national goal of achieving social justice and equitable development. Based on Law Number 1 of 2022 and Government Regulation Number 1 of 2024, regions are allowed to use creative financing patterns, including funding synergies, to fund their priority programs. In this case, qualitative descriptive methods are used to describe and interpret funding synergies as a solution to improve the results of poverty and unemployment management programs. It also helps overcome the fiscal gap of the APBD and the challenges of Baznas Cilegon in optimizing ZIS collection. To ensure the effectiveness of funding synergies, a SWOT analysis is used to evaluate internal and external factors that influence this strategy. Based on this analysis, the recommended steps include: establishing clear regulations, integrating data, synergizing planning and implementation, optimizing ZIS collection through the Zakat Collection Unit (UPZ), establishing an effective work team for coaching and supervision, and increasing public literacy and transparency through the use of information technology. These steps aim to increase public trust in Baznas and the Cilegon City Government and ensure accountability and transparency in ZIS management.